Evaluation of NiCoCrAlY coatings deposited on superalloy with novel cold spray process. (12th January 2015) - Kalsi, S. B. S.; Sidhu, T. S.; Karthikeyan, J.; Singh, H.
Abstract : The coating is considered as one of the best solutions to enhance the life of engineering components against hot corrosion. In the present study the NiCoCrAlY coating was successfully deposited on Superni 600 superalloy with cold spray process. The microstructure of the developed coating is appropriate to protect the components of power plant industry against hot corrosion. The evaluation of the coating has been done for porosity, microhardness, microstructure and phase formation with the help of optical microscopy, scanning electron microscopy (SEM)/ Energy Dispersive Spectroscopy (EDS) and X-ray diffraction (XRD) examination.